Critical view of the supranational and national regulations on violence against women - Silva Villacorta, Susana Paola (2021)
Supranational and national regulations have recognized the rights of all people in general, proscribing discrimination based on sex. In recent decades, the term “gender” has been introduced in order to protect the rights of women and eliminate violence against them. However, gender ideology does not lay its foundations in reality and neither does it serve its intended purpose. To achieve a life free of violence, we must begin by recognizing that all human beings are people, that dignity is an inherent quality of every human being and that, for this reason, we are all subjects of law, deserving of respect and treatment. according with our nature. Men and women share the same dignity, but at the same time we are different, which makes us complementary. Differences, taking into account the dignity and freedom of each one, are wealth, they are not the cause of violence.